The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1038/s41598-021-88551-7
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal diagnosis of placenta accreta spectrum after in vitro fertilization-embryo transfer: a systematic review and meta-analysis

Abstract: Increasing evidence suggests a relationship between in vitro fertilization-embryo transfer (IVF-ET) and placenta accreta spectrum (PAS). Some studies have reported a lower rate of antenatal diagnosis of PAS after IVF-ET compared to PAS with spontaneous conception. This study aimed to review the diagnostic accuracy of PAS after IVF-ET and to explore the relationship between IVF-ET pregnancy and PAS. According to the PRISMA guidelines, a comprehensive systematic review of the literature was conducted through Aug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 54 publications
2
32
0
Order By: Relevance
“…Pregnant women with endometriosis are more likely to use ART to conceive than those without endometriosis; however, ART-conceived pregnancies are associated with an increased prevalence of PASD [ 15 ]. Furthermore, recent systematic reviews have reported that women with endometriosis are more likely to have placenta previa than those without endometriosis.…”
Section: Introductionmentioning
confidence: 99%
“…Pregnant women with endometriosis are more likely to use ART to conceive than those without endometriosis; however, ART-conceived pregnancies are associated with an increased prevalence of PASD [ 15 ]. Furthermore, recent systematic reviews have reported that women with endometriosis are more likely to have placenta previa than those without endometriosis.…”
Section: Introductionmentioning
confidence: 99%
“…Although various factors (advanced maternal age, ART pregnancy, maternal smoking, etc.) are correlated with a higher rate of PP [ 100 , 101 , 102 ], most studies [ 7 , 8 , 11 , 25 , 26 , 27 , 29 , 30 , 31 , 32 , 35 , 36 , 37 ] did not perform a multivariate analysis with adjustments for obstetric background; thus, our study cannot distinguish endometriosis as an independent risk factor for PP due to the confounding factors.…”
Section: Discussionmentioning
confidence: 94%
“…This study suggested that PP complicated with endometriosis appears to be a high risk factor for postpartum hemorrhage; however, the reason for increased intraoperative bleeding remains unclear. Although the results from this study are unique, there are still some concerns regarding the diagnosis of endometriosis [ 100 , 101 , 102 ]. For example, among the 24 patients, seven had a history of endometriosis, 12 were confirmed to have endometriosis by intraoperative findings, and the remaining cases were suspected to have endometriosis based on the infeasibility of uterine exteriorization due to extrauterine posterior wall adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…A risk of bias assessment was performed using the Risk Of Bias In Non-randomized Studies-of Interventions (ROBINS-I) tool, as previously performed [ 15 , 16 , 17 , 18 , 19 ].…”
Section: Methodsmentioning
confidence: 99%